The genetics of overwintering performance in two-year old common carp and its relation to performance until market size - Prchal, Martin; Kause, Antti; Vandeputte, Marc; Gela, David; Allamellou, Jean-Michel; Kumar, Girish; Bestin, Anastasia; Bugeon, Jérôme; Zhao, Jinfeng; Kocour, Martin (PloS one, 2018)
Using farmed common carp, we investigated the genetic background of the second year overwintering performance and its relation to the performance during the third growing season and at market size. The experimental stock was established by partial factorial design with a series of 4 factorial matings of 5 dams and 10 sires each. The families were reared communally and pedigree was re-constructed with 93.6% success using 12 microsatellites on 2008 offspring. Three successive recordings (second autumn, third spring, and third autumn-market size) covering two periods (second overwintering, third growing season) were included. Body weight, Fulton's condition factor and percent muscle fat content were recorded at all times and headless carcass yield and fillet yield were recorded at market size. Specific growth rate, absolute and relative fat change and overall survival were calculated for each period. Heritability estimates were significantly different from zero and almost all traits were moderately to highly heritable (h2 = 0.36-1.00), except survival in both periods and fat change (both patterns) during overwintering (h2 = 0.12-0.15). Genetic and phenotypic correlations imply that selection against weight loss and fat loss during overwintering is expected to lead to a better winter survival, together with a positive effect on growth in the third growing season. Interestingly, higher muscle fat content was genetically correlated to lower survival in the following period (rg = -0.59; -0.53, respectively for winter and the third summer). On the other hand, higher muscle fat was also genetically linked to better slaughter yields. Moreover, selection for higher condition factor would lead to better performance during winter, growing season and at market size.
Keywords: fenotyp; Male; Phenotype; maso; chov zvířat; kvantitativní znak dědičný; mikrosatelitní repetice; kapři; mužské pohlaví; Models, Genetic; Body Weight; Microsatellite Repeats; Animals; ženské pohlaví; Quantitative Trait, Heritable; zvířata; Animal Husbandry; složení těla; Carps; modely genetické; Body Composition; Meat; Female; tělesná hmotnost